N-benzoylphenylhydroxylamine and its analogues - Majumdar, Anil Kumar, 1910- (International series of monographs in analytical chemistry, 1972)
International Series of Monographs in Analytical Chemistry, Volume 50: N-Benzoylphenylhydroxylamine and its Analogues covers the analytical applications of the organic hydroxylamine derivatives. This book is composed of seven chapters, and starts with a brief historical account of the uses of organic reagents in inorganic analysis. The next chapter discusses some basic physico-chemical factors associated with the constitution of a good reagent, including some fundamental ideas about the type and nature of the principal reactive and other groupings in the ligand. A chapter deals with the inclus.